Some Discussion Issues in Environmental Forensics - Elena I. Maiorova (Теория и практика судебной экспертизы, 2017)
Environmental forensic investigations are increasingly being used to address diagnostic and situational objectives in the criminal, as well as civil, administrative, and arbitration process. Although they offer no identification solutions, the findings of such investigations can nevertheless be quite valuable. Assessment of replacement costs in cases involving damage to environmental compartments is of particular pertinence. In the long term this field of inquiry can be expanded by integrating the mechanism of ecosystem service accounting into forensic analysis. The relevance of environmental forensic services, their evolution and optimization largely depend on the accuracy of designations selected for different categories of forensic investigation. For example, it seems plausible that investigation of waste disposal facilities should be approached as a separate field of inquiry. At the same time, it makes sense to organize the training of specialists across several related forensic disciplines at once, rather than keep it limited to narrow fields of study.